👤

Rozwiąż równania
f) 2/5 (3 - x) = -2
g) 3/4 (2 – 3x) = -6
h) 1/5 (x – 3) = 9 - x

Proszę jak najszybciej z obliczeniami


Odpowiedź :

Odpowiedź:

2/5(3-x)=-2=x=8

3/4(2-3x)=-6=x=10/3

1/5(x-3)=9-x=x=8

Odpowiedź:

f)

2/5(3-x)=-2

6/5-2/5x=-2

-2/5x=-2-1 1/5

-2/5x=-3 1/5

-2/5x=-16/5   /*(-5/2)

x=(-16/5)*(-5/2)

x=16/2

x=8

g)

3/4(2-3x)=-6

6/4-9/4x=-6

-9/4x=-6-1 2/4

-9/4x=-7 2/4

-9/4x=-30/4    /*(-4/9)

x=(-30/4)*(-4/9)

x=30/9

x=3 3/9

x=3 1/3

h)

1/5(x-3)=9-x

1/5x-3/5=9-x

1/5x+x=9+3/5

1 1/5x=9 3/5

6/5x=48/5   /*5/6

x=48/5*5/6

x=8

Szczegółowe wyjaśnienie: